If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13u + -11u + 1 = -19 Reorder the terms: 1 + 13u + -11u = -19 Combine like terms: 13u + -11u = 2u 1 + 2u = -19 Solving 1 + 2u = -19 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2u = -19 + -1 Combine like terms: 1 + -1 = 0 0 + 2u = -19 + -1 2u = -19 + -1 Combine like terms: -19 + -1 = -20 2u = -20 Divide each side by '2'. u = -10 Simplifying u = -10
| 1.82-4.3m=6.46m-9.1 | | -4q-4q-5q+(-10)=3 | | 2(h+2)=h+20 | | -4q-4q-5g+(-10)=3 | | r+3r-3=17 | | -v-(-13v)-2v-(-18v)-18v=-20 | | 1.82-4.6m=6.46m-9.1 | | 3j-3j+3j=18 | | 5p-11=21 | | -6k-(-6k)+(-k)+14k+(-18k)=15 | | -20x-(-14x)+-9x-(-14x)=9 | | X*2-2X=3 | | (400y+250x)=21750 | | (400x+250y)=21750 | | 2x-5y/4x-5y=dy/dx | | y=a-b | | 2x-5y/4x-5y | | 4X+5+3X+4=X | | 3(6-7x)=7(5x-1) | | 5p=3p-42 | | 658/245 | | 500*20/100 | | 19-9x=x+13 | | 19-9x=-4+13 | | 19-9x=4+13 | | 19-9x=9+13 | | sen^4x-cos^4x=0 | | -24a^3+54a^2=30 | | -2-3=3x+10 | | -2-3x=6+10 | | -2-3x=2+10 | | -2-3x=3+10 |